2013
DOI: 10.5194/acp-13-8607-2013
|View full text |Cite
|
Sign up to set email alerts
|

Brown carbon: a significant atmospheric absorber of solar radiation?

Abstract: Abstract. Several recent observational studies have shown organic carbon aerosols to be a significant source of absorption of solar radiation. The absorbing part of organic aerosols is referred to as "brown" carbon (BrC). Using a global chemical transport model and a radiative transfer model, we estimate for the first time the enhanced absorption of solar radiation due to BrC in a global model. The simulated wavelength dependence of aerosol absorption, as measured by the absorption Ångström exponent (AAE), inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

32
577
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 688 publications
(613 citation statements)
references
References 57 publications
32
577
3
1
Order By: Relevance
“…Due to their strong absorption in the near-ultraviolet and visible regions, nitrated phenols are classified as poorly characterized brown carbon (BrC) (Desyaterik et al, 2013;Teich et al, 2017). Though the absorption of BrC is weak compared to that of black carbon (BC), it can enhance the absorption of solar radiation and may have an indirect effect on regional climate (Feng et al, 2013;Mohr et al, 2013;Laskin et al, 2015;Lu et al, 2015;Zhao et al, 2015). Recent studies have shown that several semivolatile nitrated phenols, including nitrophenol, nitrocatechol, and methyl-nitrocatechol (NC), are important photochemical oxidation products of gas-phase precursors, which may play a part in the formation of secondary organic…”
Section: Introductionmentioning
confidence: 99%
“…Due to their strong absorption in the near-ultraviolet and visible regions, nitrated phenols are classified as poorly characterized brown carbon (BrC) (Desyaterik et al, 2013;Teich et al, 2017). Though the absorption of BrC is weak compared to that of black carbon (BC), it can enhance the absorption of solar radiation and may have an indirect effect on regional climate (Feng et al, 2013;Mohr et al, 2013;Laskin et al, 2015;Lu et al, 2015;Zhao et al, 2015). Recent studies have shown that several semivolatile nitrated phenols, including nitrophenol, nitrocatechol, and methyl-nitrocatechol (NC), are important photochemical oxidation products of gas-phase precursors, which may play a part in the formation of secondary organic…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large BB emissions of greenhouse gases and BC, it has been assumed that BB OA contributes to negative radiative forcing by BB overall. However, the overall BB forcing could be positive if the emitted weakly-absorbing OA known as brown carbon (BrC) is sufficiently absorbing and long lived 20 (Feng et al, 2013;Jacobsen, 2014;Saleh et al, 2014;Forrister et al, 2015). This could generate a positive feedback with the expected increase in BB due to a warming climate (Feng et al, 2013;Doerr and Santin, 2016;Bowman et al, 2017).…”
mentioning
confidence: 99%
“…However, the overall BB forcing could be positive if the emitted weakly-absorbing OA known as brown carbon (BrC) is sufficiently absorbing and long lived 20 (Feng et al, 2013;Jacobsen, 2014;Saleh et al, 2014;Forrister et al, 2015). This could generate a positive feedback with the expected increase in BB due to a warming climate (Feng et al, 2013;Doerr and Santin, 2016;Bowman et al, 2017). Thus, comprehensive understanding of wildfire contributions to air quality and climate requires further evaluation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Light absorbing organic carbon in atmospheric aerosol (brown carbon or BrC) has been shown to impact radiative forcing with an estimated contribution of 19% to total aerosol absorption globally (Feng et al, 2013). AERONET measurements over California have shown that in the brown carbon region (440 nm), brown carbon absorption is 40% of that attributed to elemental carbon (Bahadur et al, 2012).…”
Section: Introductionmentioning
confidence: 99%